Adolescents in situations of poverty: resilience and vulnerabilities to sexually transmitted infections - Maria Isabelly Fernandes da Costa; Raelson Ribeiro Rodrigues; Rayssa Matos Teixeira; Paulo Henrique Alexandre de Paula; Izaildo Tavares Luna; Patrícia Neyva da Costa Pinheiro
ABSTRACT Objective: To analyze the association between vulnerabilities to Sexually Transmitted Infections (STIs/HIV/AIDS) of adolescents in poverty and their level of resilience. Method: Cross-sectional study with 287 students between 11 and 17 years old in a school in the outskirts of Fortaleza-Ce. The study was conducted from August to October 2016. Three instruments related to characterization, vulnerability to STIs/HIV/AIDS and resilience were used. The association between the instruments was calculated using the Mann-Whitney and Kruskal-Wallis tests. Association between vulnerability to STIs/HIV/AIDS and resilience was assessed through the Spearman's correlation coefficient. Statistical significance was set at p<0.05. Results: There was a significant association between the factors "housing" (p=0.022), "family income" (p=0.037) and vulnerability to STIs/HIV/AIDS. Adolescents whose father has completed high school (p=0.043) have moderately high resilience. Conclusion: Adolescents with low socioeconomic status and who live on less than a minimum wage tends to be more susceptible to vulnerabilities to STIs/HIV/AIDS and to have low resilience.